1986
DOI: 10.1007/bf01727529
|View full text |Cite
|
Sign up to set email alerts
|

Left heart function in chronic obstructive lung disease

Abstract: In patients with varying degrees of chronic obstructive pulmonary disease (COPD), simultaneous measurements of central hemodynamics and left ventricular radionuclide ventriculograms at rest and during exercise were made. In 21 of these patients, satisfactory echocardiograms could be performed. In seven of the patients, arterial blood pressure at rest was increased. Decreased compliance of the left ventricle was thought to be present in patients with COPD and additional arterial hypertension. The left ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Changes in the LV filling rate do not seem to be the consequence of a LV systolic dysfunction, because the parameters of LV systolic function were similar in both groups. This result is in agreement with previous findings in patients with COPD (22)(23)(24). Moreover, there was no evidence of LV hypertrophy in our COPD group, which might have explained LV filling abnormality.…”
Section: Discussionsupporting
confidence: 95%
“…Changes in the LV filling rate do not seem to be the consequence of a LV systolic dysfunction, because the parameters of LV systolic function were similar in both groups. This result is in agreement with previous findings in patients with COPD (22)(23)(24). Moreover, there was no evidence of LV hypertrophy in our COPD group, which might have explained LV filling abnormality.…”
Section: Discussionsupporting
confidence: 95%
“…In summary, LVEF seems to be normal in COPD patients without recognized cardiovascular comorbidity 31–37 (Table S4 in the online supporting information). In those with an affected right heart, generally lower but still normal ejection fractions were found 32,34,36,37 …”
Section: Prevalence Of Heart Failure In Copdmentioning
confidence: 96%
“…In a large cohort of stable emphysema patients without a history of cardiovascular disease, mean pulmonary capillary wedge pressure was 14 mm Hg, 35 indicating mild LVDD. Some smaller studies showed no LVDD in comparable patients 32,36,38 (Table S5 in the online supporting information). Boussuges et al .…”
Section: Prevalence Of Heart Failure In Copdmentioning
confidence: 99%
“…Hyperinflation has been linked to low cardiac output in patients with COPD [10], in part by limiting left ventricular stroke volume [11,12]. Reversing hyperinflation through lung volume reduction surgery improves cardiac function at rest and during exercise [13,14].…”
Section: Introductionmentioning
confidence: 99%